The role and impact of technology in college and university honor systems - Lesperance, Shirley Dawn (Kansas State University, 2010)
An honor system is a governing body within an education system that “includes one or more of the following elements: a written pledge in which students affirm that their work will be or has been done honestly; the majority of the judiciary that hears alleged violations of academic dishonesty is compromised of students, or the chair of this group is a student; unproctored examinations; and a clause that places some degree of obligation on students to report incidents of cheating they learn about or observe” (McCabe, Trevino, & Butterfield, 2001). Institutions from high schools to major universities are establishing such systems as a way to preserve the integrity of their diplomas and degrees. Research has shown that “up to 70% of college students cheat at some point prior to graduation” (Whitley, 1998). What is more alarming is the number of these students are using technology in an attempt to get ahead. In this report, I intend to show how technology affects different aspects of honor systems. First I will briefly discuss the history of honor systems and how the changes in technology have affected them. I will define common terms and ideas associated with today’s honor systems, and then discuss how sanctioning has evolved. Next, I will explore the role changing technology plays in honor pledge/code violations. Specifically, I will address how honor systems are addressing the growing problem of technology being used in cases of academic dishonesty, unfortunate uses of new technology in the classroom, and how on-line learning is impacting the work of honor systems. Lastly, through conversations with people working in honor system offices nationwide, I will highlight the roles and impact that technology is playing on their campuses.
Keywords: Honor; System; Technology; Education, Higher (0745)